2021
DOI: 10.1186/s13018-021-02222-x
|View full text |Cite
|
Sign up to set email alerts
|

Locked compression plating versus retrograde intramedullary nailing in the treatment of periprosthetic supracondylar knee fractures: a systematic review and meta-analysis

Abstract: Background Periprosthetic fractures of the distal femur above a total knee arthroplasty (TKA) have traditionally been managed by locking compression plating (LCP). This technique is technically demanding and is associated with high rates of non-union and revision. More recently, retrograde intramedullary nailing (RIMN) has been proposed as an acceptable alternative. This meta-analysis aims to evaluate clinical outcomes in patients with periprosthetic supracondylar femoral fractures who were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…The KSS scores of the patients after RIMN with a femoral nail for distal femur fractures range between 70 to 80. The mean KSS score in this study was consistent with the previous literature (12) and the use of a tibial nail did not end up with an inferior outcome.…”
Section: Discussionsupporting
confidence: 90%
“…The KSS scores of the patients after RIMN with a femoral nail for distal femur fractures range between 70 to 80. The mean KSS score in this study was consistent with the previous literature (12) and the use of a tibial nail did not end up with an inferior outcome.…”
Section: Discussionsupporting
confidence: 90%
“…[12][13][14][15] While small differences could be identified in biomechanical and clinical studies, pooled data suggests that there is no discernable difference between the 2 treatment types. [16] Recently, several authors have supported the application of combined PN constructs for use in challenging supracondylar fractures such as those with poor-quality or osteoporotic bone, a short distal segment, nonunion, malunion, or peri-implant lesions. [1][2][3] In these situations, fixation strength and rigidity may help prevent loss of alignment and improve healing.…”
Section: Discussionmentioning
confidence: 99%
“…If considering plating the less invasive stabilization system with cerclage wiring and the use of a polyaxial locking plate is the preferable technique today with regard to soft tissue preservation, but requires an experienced surgeon and is more difficult to perform in complex fractures. 27,28 Biomechanical studies have shown that for PSF after TKA, RIMN can guarantee greater stability in patients with a posterior cruciate ligament retaining femoral TKA component 8 and this technique may improve the rate of the union while decreasing soft-tissue trauma. 1 Makinen et al 10 compared biomechanical results of locking plates and retrograde intramedullary nails in periprosthetic supracondylar fractures of the distal femur.…”
Section: Discussionmentioning
confidence: 99%